Propeller Flaps for Hand and Digit Reconstruction - Tos, Pierluigi; Crosio, Alessandro; Pugliese, Pierfrancesco; Georgescu, Alexandru Valentin (Seminars in Plastic Surgery, 2020)
The reconstruction of soft tissue defects of the hand, as seen often after trauma or tumor excision, is a challenge due to the great differentiation of tissues depending on the hand area involved. The classical intrinsic “workhorse flaps” of the hand are associated with a significant donor-site morbidity. Capturing perforator vessels in discrete donor areas can reduce the amount of soft tissue that has to be dissected and included in what now would be a perforator flap, while also insuring robust vascularization of those transferred tissues. Moreover, the presence of perforator vessels both on the dorsal and volar sides of the hand allows harvest of perforator flaps that will respect the like-with-like principle by maintaining the main characteristics of volar and dorsal skin as desired. However, the dissection of these flaps, especially those based on volar palmar and digital perforators, still requires microsurgical skills to preserve the fine vascularization of these flaps. These small flaps are also amenable for application of the propeller flap concept. This is an especially valuable means for preserving the length of an amputated finger where bone is exposed by using more proximal uninjured tissues. Although in general only a short dissection is required to raise a propeller flap in this region, most often the donor site will have to be closed by a skin graft.
Keywords: hand; perforator flaps; digit; propeller flaps; amputation